ANALYSIS OF THE MOST SENSITIVE TOLL ROAD SERVICE PERFORMANCE BASED ON USER PERCEPTION AND INFLUENCED FACTORS - Medi Yandriguna; Muhammad Karami; Rahayu Sulistyorini; Masdar Helmi; Niken DWSBU (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to evaluate the service performance of the Terbanggi Besar–Pematang Panggang–Kayu Agung (TERPEKA) toll road section based on user perceptions and to identify the factors influencing toll road service performance. The analysis employs the Service Quality (SERVQUAL) method and Important Performance Analysis (IPA) to measure the gap between user expectations and perceived performance, complemented by factor analysis to determine the dominant influencing factors. The results indicate that the overall service quality of the TERPEKA toll road remains unsatisfactory, as all SERVQUAL dimensions show quality (Q) values below 1. IPA results reveal several priority attributes requiring immediate improvement, particularly road surface conditions, street lighting, modern toll facilities, road geometry comfort and safety, and rest area comfort and security. Furthermore, factor analysis identifies three main factors influencing service performance—service factors, quality factors, and performance factors—which together explain 77.33% of the total variance. The service factor is the most dominant, contributing 66.131% of the variance, followed by quality and performance factors. These findings highlight the need for targeted improvements in infrastructure quality and service management to enhance user satisfaction on the TERPEKA toll road.